Does Money Matter: Earnings Patterns Among a National Sample of the US State Governmental Public Health Agency Workforce - Castrucci, Brian C. (J Public Health Manag Pract, 2015)
Earnings have been shown to be a critical point in workforce recruitment and retention. However, little is known about how much governmental public health staff are paid across the United States. OBJECTIVE: To characterize earnings among state health agency central office employees. DESIGN: A cross-sectional survey was conducted of state health agency central office employees in late 2014. The sampling approach was stratified by 5 (paired HHS) regions. Balanced repeated replication weights were used to correctly calculate variance estimates, given the complex sampling design. Descriptive and bivariate statistical comparisons were conducted. A linear regression model was used to examine correlates of earnings among full-time employees. SETTING AND PARTICIPANTS: A total of 9300 permanently employed, full-time state health agency central office staff who reported earnings information. MAIN OUTCOME MEASURE: Earnings are the main outcomes examined in this article. RESULTS: Central office staff earn between $55 000 and $65 000 on average annually. Ascending supervisory status, educational attainment, and tenure are all associated with greater earnings. Those employed in clinical and laboratory positions and public health science positions earn more than their colleagues in administrative positions. Disparities exist between men and women, with men earning more, all else being equal (P < .001). Racial/ethnic disparities also exist, after accounting for other factors. CONCLUSIONS: This study provides baseline information to characterize the workforce and key challenges that result from earnings levels, including disparities in earnings that persist after accounting for education and experience. Data from the survey can inform strategies to address earnings issues and help reduce disparities.